Health care professionals report positive experience with a breastfeeding training program based on the Baby-Friendly Hospital Initiative for Neonatal Intensive Care. Issue 1 (February 2023) - Gerhardsson, Emma; Oras, Paola; Mattsson, Elisabet; Blomqvist, Ylva Thernström; Funkquist, Eva-Lotta
Abstract: Support from health care professionals (HCPs) with good knowledge and positive attitudes toward breastfeeding has been associated with better breastfeeding outcomes in the mothers of preterm infants. The aim of the study was to describe HCPs' experiences of a breastfeeding training program. A total of 48 specialist registered nurses, registered nurses, assistant nurses and physicians working at a neonatal intensive care unit attended a breastfeeding training program and answered a questionnaire including Likert scales and open-ended questions. The participants reported that their interest in breastfeeding had increased as a median (range) of 10 (8–10) on a 10-point scale and rated to what extent they had received new tools for breastfeeding support as a median of 10 (8–10) after training. There were no differences in the median between different professions' ratings. Qualitative content analysis of the open-ended questions resulted in two categories: Discussions of the case scenarios in the group and Knowledge regarding breastfeeding . The results showed that discussions based on breastfeeding scenarios were perceived as valuable; the health care professionals reported receiving new knowledge and useful practical skills. This program was shown to increase health care professionals' interest in breastfeeding and is useful for different health care professions.